Pengaruh Senam Hamil Terhadap Penurunan Nyeri Punggung Bawah Pada Ibu Hamil Trimester II Dan III Di Puskesmas Mayor Umar Kota Tanjungbalai Tahun 2022 - Ade Rachmat Yudianto; Ingka Kristina Pangaribuan; Damayanty S (Jurnal Sains dan Kesehatan, 2022)
Pregnancy is defined as fertilization or union of spermatozoa and ovum and followed by nidation or implantation. If calculated from the fertility phase until the birth of the baby, a normal pregnancy will take place within 40 weeks or 10 lunar months or 9 months according to the international calendar. Pregnancy lasts in three trimesters, the first trimester lasts 13 weeks, the second trimester 14 weeks (weeks 14 to 27), and the third trimester 13 weeks (weeks 28 to 40)). Pregnancy is a normal process that produces a series of physiological and psychological changes in pregnant women Lower back pain during pregnancy occurs due to changes in pregnancy hormones which increase relaxant hormones (hormones that make muscles relax and become weak), this affects the flexibility of the ligament tissue which ultimately increases joint mobility in the pelvis and will have an impact on spinal and pelvic instability and cause pain. on the back. Other predisposing factors that cause back pain are related to weight gain, changes in body posture due to uterine enlargement, previous back pain and repetitive stretching. Apart from that, back pain is also felt due to incorrect body posture when sitting, standing, lying down and even when doing household activities